Detecção de Histophilus somni (Haemophilus somnus) no sêmen bovino mediante reação em cadeia pela polimerase (PCR) - Dias, Francisca Elda Ferreira; Nunes, Caris Maroni [UNESP]; Cavalcante, Tânia Vasconcelos; Souza, Juliano Franco de [UNESP]; Barbosa, Silvia Minharro; Castro, Andréa Azevedo Pires de; Moraes Jr., Felipe de Jesus [UNESP]; Oliveira, Cláudia Marinovic; Garcia, José Fernando [UNESP] (Pontificia Universidade Catolica do Parana - PUCPR, 2014)
The present study evaluated the use of PCR for Histophilus somni detection in bovine semen. Semen samples were experimentally infected with H. somni at dilutions ranging from 107 to 101 bacteria/mL and subjected to DNA extraction by the phenol/chloroform method, followed by PCR amplification. The amplification products were analyzed by electrophoresis in 8% acrylamide gel. The oligonucleotide primers used yielded an amplification fragment of 400 base pairs from the bacterial DNA. Positive amplification was obtained even for the 101 bacteria/mL dilution. PCR proved to be an efficient method for the detection of H. somni. The results obtained in this study have brought relevant information for the diagnosis of H. somni, justifying the need for the diagnosis of this bacterium in bulls, especially in semen samples that should be free of contamination. The PCR method has shown to be a useful tool for the quality control of semen produced in artificial insemination centers.

O presente estudo avaliou o uso da PCR para a detecção do Histophilus somni no sêmen bovino. Amostras de sêmen foram contaminadas experimentalmente com H. somni diluída em escalas de 107 a 101 bactérias/ mL, submetidas à extração de DNA pelo método de fenol/clorofórmio e amplificadas pela PCR. Os produtos da amplificação do DNA foram analisados por eletroforese em gel de acrilamida 8%. Por meio de oligonucleotídeos iniciadores obteve-se a amplificação de um fragmento de 400 pares de bases a partir do DNA da bactéria. Conseguiu-se amplificação positiva até na diluição de 101 bactérias/mL. A PCR mostrou-se eficiente na detecção de H. somni. O resultado disponibiliza conhecimento relevante para o diagnóstico de H. somni, justificando a necessidade do diagnóstico dessa bactéria em reprodutores, especialmente em amostras de sêmen, que deveriam estar livres de qualquer contaminação. A PCR mostrou-se como uma valiosa ferramenta no controle da qualidade do sêmen produzido em centrais de inseminação artificial.
Detection of Histophilus somni (Haemophilus somnus) in bovine semen using polymerase chain reaction (PCR)
Keywords: Cattle; Semen; Histophilus somni; PCR; Bovino; Sêmen; Histophilus somni; PCR